Strategi Penguatan Ketahanan Pangan Berbasis Komunitas di Kesepuhan Sinarresmi dalam Mendukung Pertahanan Negara - Wenni Mustika; Hikmat Zakky Almubaraq; Untung Hartono (Pusat Riset dan Inovasi Nasional, 2025)
Kesepuhan Sinarresmi has long been recognized for implementing a community-based food resilience system rooted in indigenous customary law. This study on Kesepuhan Sinarresmi aims to analyze the strategy for strengthening food resilience using an in-depth Qualitative Case Study approach. Data was collected through interviews, participant observation, and combined with a review of current literature related to food resilience, customary institutions, and non-military defense. The findings reveal that the food resilience strengthening strategy in Kasepuhan Sinarresmi proves effective through the integration of socio-cultural institutions and ecologically aligned agronomic practices.This food resilience system is sustained by: 1) Customary Institutions governing access and distribution; 2) The Leuit Institution (communal granary) serving as an inter-generational strategic reserve; and 3) The diversification of 68 Local Rice Varieties, which enhances resilience against crop failure and climate change. This model affirms the principle of community food sovereignty and functions as a robust logistical system, simultaneously serving as a best practice for non-military national defense.Based on the study conducted in Kesepuhan Sinarresmi, it is recommended that the Indigenous Community food reserve system be formally recognized and integrated into a policy framework. This is proposed as a strategic effort to strengthen national resilience against crises